Curso-taller sobre metodologias de investigacion en bosques secundarios, 10-20 de Febrero de 1998, Pucallpa, Peru: memorias (CIFOR and CATIE, 1998)
This document summarises participants' reports based on field-oriented problems aimed at testing research methodologies from both the biophysical and socioeconomic components of secondary forest management. This 10-day workshop was held in Eastern Amazonia (Pucallpa, Perú) with the participation of professionals from Perú, Nicaragua, Brazil, and Bolivia.